Nasser and Park: Development, state building, and elite consolidation - Choi, David Wooil (AUC Knowledge Fountain, 2018)
This thesis examines the relationship between elites and development and state building. It looks at how elite consolidation does or does not affect development and state building. It does this in the context of the cases of Egypt under Gamal Abdal Nasser and Korea under Park Chunghee. The thesis initially puts forward the argument that Korea's advantages from the colonial era set the basis for later development and state building, and paved the way for elite consolidation into the 1960s. However, the thesis ultimately finds that while Korea may have had some advantages from the colonial era that helped in development and state building, this was but one factor of the ability of elites to consolidate well. It ultimately argues that the ability of elites to effectively consolidate is connected to the efficiency of the bureaucracy and exogenous catastrophic circumstances, which are in turn connected to the success of development and state building processes.